From chaos to control - experiences of healthcare workers during the early phase of the COVID-19 pandemic: a focus group study - Fredrik Rücker; Maria Hårdstedt; Sekai Chenai Mathabire Rücker; Emma Aspelin; Alexander Smirnoff; Anders Lindblom; Catharina Gustavsson (BMC, 2021)
Abstract Background The Coronavirus disease 2019 (COVID-19) pandemic has caused overwhelming challenges to healthcare systems worldwide. Healthcare workers (HCWs) have faced particular challenges: being exposed to the coronavirus SARS-CoV-2 and caring for patients having a new and potentially life-threatening disease. The aim of this study was to explore how HCWs in the Swedish healthcare system perceived their work situation during the first phase of the COVID-19 pandemic in 2020. Methods Focus group discussions and interviews with HCWs were performed from June to October 2020 in one Swedish healthcare region. A purposeful sampling approach was used to select a variety of professions (physicians, nurses, nurse aides and cleaners) and workplaces (hospital inpatient wards, emergency department, nursing home and home care service). Qualitative content analysis was used for data analysis. Results In total, 51 HCWs participated in eight focus group discussions and one HCW participated in an individual interview. The content analysis identified two main categories: 'Concerns about the risk of infection and transmission of infection to others', and 'Transition from chaos to managing in a new and challenging work situation'. The findings revealed how HCWs perceived working conditions, including experiences of fear for personal health, confusion and uncertainty regarding personal protective equipment and infection prevention and control (PPE/IPC), and fear of infecting others. Both fearful and appreciating attitudes were achieved from the surrounding community. Helpful strategies for transition from chaos to control were lifted i.e. present and supportive leadership, and finding comfort and strength in the working team. Both helplessness and meaningfulness were described when caring for COVID-19 patients. Conclusions This study provides unique insights into HCWs experiences of an extremely challenging work situation during the first phase of the COVID-19 pandemic, including feelings of stress and insecurity in a chaotic and hazardous working environment. But there is also mitigation of these challenges and even positive experiences including feelings of safety and meaningfulness. To enhance safety among HCWs in healthcare crises such as the COVID-19 pandemic, the findings highlight the importance of avoiding confusion about PPE/IPC, having a supportive healthcare leadership and ensuring accurate information provision about virus transmission to the public.